2007
DOI: 10.1177/1524838007307295
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Among Female Veterans

Abstract: This article reviews the literature documenting the nature and prevalence of traumatic experiences, trauma-related mental and physical health problems, and service use among female veterans. Existing research indicates that female veterans experience higher rates of trauma exposure in comparison to the general population. Emerging data also suggest that female veterans may be as likely to be exposed to combat as male veterans, although not as directly or as frequently. Female veterans also report high rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
199
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(210 citation statements)
references
References 69 publications
8
199
3
Order By: Relevance
“…26 Other limitations of current literature on ACEs among veteran women include the primary focus on sexual abuse, the use of convenience samples, and a lack of a non-veteran comparison group, limitations which the current study adresses. 27,28 Unlike other studies examining the association between ACEs and military service, 2,25 the focus of this study was specifically on women veterans: those who had served in, and separated from, military service. The purposes of the present study were to document the prevalence of ACEs among women veterans compared with women non-veterans, assess a range of physical and mental health outcomes among women veterans and non-veterans, and determine the role of ACEs in health differences among veteran and non-veteran women.…”
Section: Introductionmentioning
confidence: 99%
“…26 Other limitations of current literature on ACEs among veteran women include the primary focus on sexual abuse, the use of convenience samples, and a lack of a non-veteran comparison group, limitations which the current study adresses. 27,28 Unlike other studies examining the association between ACEs and military service, 2,25 the focus of this study was specifically on women veterans: those who had served in, and separated from, military service. The purposes of the present study were to document the prevalence of ACEs among women veterans compared with women non-veterans, assess a range of physical and mental health outcomes among women veterans and non-veterans, and determine the role of ACEs in health differences among veteran and non-veteran women.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Previous studies show that women veterans report greater rates of trauma, 3 including sexual trauma, as well as worse mental and physical health 4 compared with women nonveterans. Nonetheless, very little is known regarding sexual behaviors and sexually transmitted infections (STIs) in this population, or whether there are differences compared with women nonveterans.…”
mentioning
confidence: 99%
“…adult sexual assault than nonveterans, 3 and abuse has been associated with adult sexual risk behaviors in the general population. 43,44 Moreover, combat exposure has been associated with increased risk taking, which may also include engaging in high-risk sexual behaviors.…”
mentioning
confidence: 99%
“…Given the rapidly increasing number of women servicemembers and veterans [5] and their increased exposure to combat [31], the number of women veterans and servicemembers with traumatic limb loss may be expected to grow, and little is known regarding their health and healthcare needs. We found that compared with men, women with traumatic limb loss had similarly high levels of persistent physical and mental health conditions.…”
Section: Discussionmentioning
confidence: 99%